Robust Tracking Control of a Quadrotor Unmanned Aerial Vehicle-Suspended Payload System - Xian, Bin; Yang, Sen (IEEE/ASME transactions on mechatronics, 2021)
In this article, the control problem for the underactuated dynamic system, which consists of a quadrotor unmanned aerial vehicle and a suspended payload is investigated under the effects of unknown exogenous disturbances. A novel nonlinear controller based on the robust integral of the sign of the error is developed to deal with the position trajectory tracking control and the antiswing control of the suspended payload with the presence of unknown air turbulence. The Lyapunov-based stability analysis is employed to prove the asymptotic stability of the closed-loop system. The real-time experimental results are presented to verify the performance of the proposed control design.